Wastewater Treatment Model in Washing Stations for Vehicles Transporting Dangerous Goods - Muha, Robert (Promet - Traffic&Transportation, 2004)
Car washing is a task performed by every passenger carowner more or less frequently, mainly to achieve a finer appearanceof the vehicle rather than for the need for cleanness.In the transport business, the owner’s concern is to presentclean and orderly vehicles on the road as a relevant external elementof order, implying good corporate image to customers. Onthe other hand, in dangerous goods transportation there areother reasons requiring special technology of washing, applicableto the transport means used, depending on the change oftype of goods in carriage, the preliminary preparation of a vehicleto load the cargo, or to undergo maintenance.Water applied in the technology of washing collects the residueof goods carried in the vehicle and is polluted to such an extentthat it cannot be discharged into sewers - nor directly into awatercourse - without previous treatment.The paper presents a solution model and a sequence oftechnological procedures involved in an efficient treatment ofthe polluted wastewater in tank wash stations, in which mostlyvehicles carrying ADR goods are washed.